2020
DOI: 10.30557/mt00147
|View full text |Cite
|
Sign up to set email alerts
|

Il Dopo di Noi: nuove alleanze tra pedagogia speciale ed economia per nuovi spazi di Qualità di Vita

Abstract: Il contributo esplora le dimensioni esistenziali ed economiche del Dopo di Noi. Gli autori, in particolare, approfondiscono le sfide che una famiglia, in cui i membri economicamente rilevanti sono in età senile, si trova ad affrontare: da un lato, le preoccupazioni per il futuro di un figlio adulto con disabilità, dall'altro, un Welfare State moderno che introduce un cambio di paradigma nella produzione e/o finanziamento dell’assistenza sociale alle persone con disabilità, anche complesse. Se, in termini econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The pandemic has had a significant psychological impact on all of us (Biffi & Galimberti, 2021;Bocci, 2021;Brook et al, 2020;Di Giandomenico, Marchetti, Fontanesi & Verrocchio, 2020) and as we have demonstrated in our previous research (Giaconi, Socci, Fidanza, Del Bianco, D'Angelo & Capellini, 2020;Giaconi, Del Bianco, Socci, Severini & D'Angelo, 2021) even more for people who already presented states of illness or disability and for their families, the impact was not only pedagogical but also due to the lack of a series of services and supports that had to guarantee the rights of care and protection (Giaconi et al, 2020;. Even under the best of circumstances, caregiving can be challenging.…”
Section: Introduction: the Pandemic And "Submerged" Familiessupporting
confidence: 67%
See 4 more Smart Citations
“…The pandemic has had a significant psychological impact on all of us (Biffi & Galimberti, 2021;Bocci, 2021;Brook et al, 2020;Di Giandomenico, Marchetti, Fontanesi & Verrocchio, 2020) and as we have demonstrated in our previous research (Giaconi, Socci, Fidanza, Del Bianco, D'Angelo & Capellini, 2020;Giaconi, Del Bianco, Socci, Severini & D'Angelo, 2021) even more for people who already presented states of illness or disability and for their families, the impact was not only pedagogical but also due to the lack of a series of services and supports that had to guarantee the rights of care and protection (Giaconi et al, 2020;. Even under the best of circumstances, caregiving can be challenging.…”
Section: Introduction: the Pandemic And "Submerged" Familiessupporting
confidence: 67%
“…In conclusion, the studies reported in this section show how the life cycle of a family with children with PIMD is full of delicate and sensitive phases both from a pedagogical and economic point of view (Giaconi et al, 2020;, even more so it is state in the period of the pandemic and post-pandemic. This period also showed, as will be specified in the next paragraph, how the family itself has been a resource for the community, addressing the challenges of daily care and care for their children.…”
Section: The Delicate Life Path Of Families With Members With Pimd In...mentioning
confidence: 87%
See 3 more Smart Citations